Learning Space Management Nurul Islam Nature School (SANI) Jember to Cultivate Children's Spirituality - Istifadah Istifadah (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Learning space is a fundamental need in education. The availability of space for educational institutions is a necessity to accommodate all learning activities. This is no exception for early childhood education. The purpose of this study was to describe and analyze the management of the learning space to foster the value of children's spirituality. The research was conducted at the Nurul Islam Islamic School (SANI) at the Nurul Islam Islamic Boarding School Jember. The study focused on the analysis of the learning space for early childhood based on the theory of (Taylor et al., 2009), as well as several other relevant theories. Data was extracted through observation, interviews, documentation and photography and analyzed in three steps: data condensation, data presentation, and drawing conclusions or verification based on source triangulation. In this study, it was found that the management of the SANI learning space is a development of Taylor theory, namely the content, context, learning process, and spiritual values of the pesantren tradition in managing the SANI learning space